Pengkondisian Udara Secara Otomatis Pada Proses Pasteurisasi Kumbung Jamur Merang Menggunakan ATMEGA8535 - Wardika, Wardika; Karsid, Karsid (Jurnal Teknologi Terapan, 2016)
In this research designed an air conditioning system that is capable of reaching temperatures needed in the pasteurization process in miniature kumbung. The temperature required is approximately 70-80oC. The temperature was maintained for 4 hours. To maintain at that temperature control system designed 'on-off' by using a microcontroller ATMega 8535. This system works by shutting down the system when the temperature has been reached and revive the system when the temperature has dropped to the lower limit temperature setpoint. The results of this research in terms of the time required for the pasteurization process kumbung automatic mushroom faster at less than 5 hours compared kumbung regular mushrooms is 7-8 hours.